Design of low- area, power fault tolerant parallel FFTs using trellis codes - NagaSaiLakshmi, B.; T, RajaSekhar. (International Journal of Engineering and Technology, 2018)
Present day electronic circuits are generally affected by the delicate mistakes. To maintain the reliability of the complex systems few techniques have been proposed. For few applications, an algorithmic - based fault tolerance (ABFT) system has attempt to abuse the algorithmic properties to identify and adjust mistakes. One example FFT used. There are various protection schemes to identify and adjust errors in FFTs. It is normal to discover various blocks are working in parallel. Recently; a new method is exploiting to implement a blame tolerance in parallel. In this work, same method is first applicable to parallel FFT and then secured methods are merged that the use of error correction codes (ECCs) and parseval checks are used to detect and correct a single bit fault. Trellis code is applied to parallel FFTs to protect the errors which are used to detect and correct a multibit faults are proposed and evaluated. The 4-point FFT is protected with the input32-bit length .Simulation and Synthesis report for FFT using ECC,SOS,ECC-SOS,Trellis codes are obtained in Xilinx software14.2v.Area,power,delay is analyzed in cadence using 90nm & 180nmTechnology.Â